স্বাধীন বাংলা বেতার কেন্দ্রের ইতিহাস - প্রধান, জাহিদ হোসেন (ঢাকা : ইত্যাদি গ্রন্থ প্রকাশ, 2008)
History of Svādhīna Bāṃlā Betāra Kendra, first independent radio station in Bangladesh started at the time of the independence struggle in 1971; contributed articles.
স্বাধীন বাংলা বেতার কেন্দ্রের মনোগ্রাম.
Donated by Akbar Ali Khan
In Bengali.
Keywords: Svādhīna Bāṃlā Betāra Kendra -- History; Radio in politics -- Bangladesh -- History; Political campaigns -- Bangladesh -- History; Bangladesh -- History -- Revolution, 1971.